2010
DOI: 10.1542/peds.2009-0634
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Environmental Predictors of Behavioral Sequelae in Children Born Preterm

Abstract: OBJECTIVE By using behavioral outcome measures of children who were born preterm, we evaluated differences between children who were born at term and children who were born at extremely low (ELBW; <1000 g) and very low birth weights (VLBW; 1000 –1499 g) and assessed the relationship of birth weight, socioeconomic status, and cognitive ability to behavioral outcome. METHODS We studied a total of 104 children (aged 7–16 years). Of these, 49 had a preterm birth (31 of ELBW and 18 of VLBW). The remaining 55 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
62
3
15

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 23 publications
(31 reference statements)
7
62
3
15
Order By: Relevance
“…These results are in agreement with those of other studies available in the literature, which reported greater vulnerability of low birth weight children exposed to risk factors of behavioral problems, especially hyperactivity (Pettersson et al, 2014;Scott et al, 2012;Singh et al, 2013) and childhood depression (Conrad et al, 2010;Hayes & Sharif, 2009;Lieshout & Boylan, 2010).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are in agreement with those of other studies available in the literature, which reported greater vulnerability of low birth weight children exposed to risk factors of behavioral problems, especially hyperactivity (Pettersson et al, 2014;Scott et al, 2012;Singh et al, 2013) and childhood depression (Conrad et al, 2010;Hayes & Sharif, 2009;Lieshout & Boylan, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Studies on the negative effects of low birth weight and their association with environmental risk factors have confirmed the correlation between biological risk factors and social adversities (Bohnert & Breslau, 2008;Conrad et al, 2010;Saur, 2012;Vanderbilt & Gleason, 2010).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…E, no estudo de Hack et al (2004), o resultado mais positivo pode estar relacionado com a idade de avaliação, já que os problemas comportamentais tendem a diminuir com a idade (Wiles et al, 2006). Quanto à escala de hiperatividade, as crianças do grupo MBP apresentaram significativamente mais dificuldades em comparação aos outros grupos de peso, o que é concordante com estudos prévios que relatam que as crianças nascidas com muito baixo peso apresentam mais dificuldades nessa área em comparação às crianças nascidas com peso normal (Conrad et al, 2009;Hack et al, 2004;Msall & Park, 2008). Por outro lado, no grupo PIG não foi observada mais dificuldade nessa escala, o que coloca em destaque uma peculiaridade desse grupo, e a relevância da comparação de critérios de estratificação com a mesma amostra.…”
Section: Discussionunclassified
“…Alguns estudos mostram que crianças nascidas com baixo peso apresentam mais problemas comportamentais em comparação às crianças nascidas com peso normal (Aarnoudse-Moens, Weisglas-Kuperus, Goudoever, & van Osterlaan, 2009;Bhutta, Cleves, Casey, Cradock, & Anand, 2002;Conrad, Richman, Lindgren, & Nopoulos, 2009;Gallo et al, 2011;Hack et al, 2004;Martins, Linhares, & Martinez, 2005;Oliveira, Enumo, Queiroz, & Azevedo Jr, 2011;Reijneveld et al, 2006;Rodrigues, Mello, & Fonseca, 2006;Wiles et al, 2006). Em estudo conduzido por Gallo et al (2011), por exemplo, foi avaliada uma coorte de 4.357 crianças, aos 11 anos, por meio do Questionário de Capacidades e Dificuldades (do inglês Strengths and Difficulties Questionnaire -SDQ), com o objetivo de verificar a associação entre o tamanho ao nascimento e SKB Correia et al problemas de saúde mental.…”
unclassified